Integration of promotion and production decisions in sales and operations planning. Issue 12 (18th June 2018) - Darmawan, Agus; Wong, Hartanto; Thorstenson, Anders
Abstract : This paper presents a new modelling framework for developing a sales and operations plan that integrates promotion and production planning decisions. We adopt a rich demand function that captures the dynamics and heterogeneity of consumer response to price promotions by simulating purchase incidence, consumer choice and quantity decisions, as well as household's inventory level. Our numerical study reveals interesting findings on the benefits of developing an integrated sales and operations plan as well as the optimal timing and number of promotions, and more importantly, how these findings are influenced by the mutual dependence of marketing- and production-related factors.